Nanoscale double-phase high-entropy zirconate fiber membrane and preparation method thereof

Nano-scale high-entropy zirconate fiber membranes were prepared by specific rare earth elements combination and electrospinning method, which solved the problems of uneven preparation and insufficient performance of high-entropy zirconate nanofibers in the prior art, and achieved high-performance anti-sintering, heat insulation and high-temperature stability.

CN120401134APending Publication Date: 2025-08-01CENT SOUTH UNIV

Patent Information

Application Number
CN202510535326.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-27
Publication Date
2025-08-01

AI Technical Summary

Technical Problem

The prior art is difficult to prepare uniform high entropy zirconate nanofibers at low temperatures, and their sintering and thermal insulation properties are poor.

Method used

A specific combination of rare earth elements (La, Sm, Gd, Dy, Yb) and Zr are used to form high-entropy zirconate fibers. Nanoscale high-entropy zirconate fiber membranes with calcinite and defective fluorite biphasic structures are prepared by electrospinning and low-temperature heat treatment process.

Benefits of technology

The uniform preparation of high-entropy zirconate fiber membranes is achieved, with good sintering resistance, thermal insulation properties and high temperature stability, and good flexibility, with room temperature thermal conductivity below 0.035W/m/K.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120401134A_ABST
    Figure CN120401134A_ABST
Patent Text Reader

Abstract

The invention discloses a nanoscale double-phase high-entropy zirconate fiber membrane and a preparation method thereof, and belongs to the field of high-entropy ceramic fiber new material preparation, and the fiber membrane is composed of continuous high-entropy zirconate fibers; the chemical structural formula of the high-entropy zirconate fiber is (La0. 2Sm0. 2Gd0. 2Dy0. 2Yb0. 2) 2Zr2O7, and the high-entropy zirconate fiber comprises a biphase structure of pyrochlore and defective fluorite. Through the cooperation of the high-entropy structural design and the electrostatic spinning-calcining method, the fiber membrane has a pyrochlore and defective fluorite double-phase structure and a small grain size, so that the fiber membrane is endowed with good anti-sintering performance, heat insulation performance and high-temperature stability, and meanwhile, the fiber membrane has certain flexibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a nanoscale dual-phase high-entropy zirconate fiber membrane and a preparation method thereof, and particularly relates to an ultra-fine nanoscale high-entropy zirconate fiber membrane material with a dual-phase structure and a preparation method thereof, belonging to the field of preparation of new high-entropy ceramic fiber materials. Background Art

[0002] Rare earth zirconates have received extensive attention due to their excellent properties such as high melting point, good chemical stability, low thermal conductivity, and high catalytic activity, and play an important role in the fields of aerospace and national defense. Rare earth zirconate fiber materials not only have the excellent physical and chemical properties of rare earth zirconate materials themselves, but also have higher high-temperature stability and lower thermal conductivity, and are a potential lightweight high-temperature thermal insulation material. However, grain growth at high temperatures can cause the ceramic fibers to sinter and break, which will further reduce the thermal insulation performance of the ceramic fibers.

[0003] With the continuous development of high-entropy materials, the concept of high entropy has also been introduced into the ceramic field. Compared with single-component ceramics, high-entropy ceramics have a large number of lattice distortions and lattice defects, which all result in excellent anti-sintering performance and thermal insulation performance of high-entropy ceramics. Undoubtedly, the structural design of high-entropy ceramics for ceramic fibers is an effective method to improve the comprehensive performance of rare earth zirconate ceramic fibers. At present, the research on high-entropy zirconate materials mainly focuses on powders and ceramics, and there is little research on high-entropy zirconate nanofibers.

[0004] Chinese patent application CN109868526A discloses a method for preparing yttrium zirconate nanofibers from a zirconium-yttrium polymer precursor. However, the fibers produced by this method have a diameter of 500 nm, rapid grain growth, and poor sintering resistance. In their article titled "High temperature and high strength Y2Zr2O7 flexible fibrous membrane for efficient heat insulation and acoustic absorption," Xie et al. used an 1100°C planar heat source device to test the thermal insulation properties of 10mm thick yttrium zirconate nanofibers. The cold end temperature was 421°C, indicating poor insulation performance. The thermal conductivity of the yttrium zirconate fiber membrane was tested using the Hot Disk transient planar heat source method, resulting in a value of 0.038 W / m / K at room temperature. Chinese patent application CN115925417 A discloses a high-entropy zirconate ceramic material with low thermal conductivity and resistance to CMAS corrosion. However, existing high-entropy zirconate materials are prepared via solid-phase reaction and co-precipitation methods. The solid-phase method, however, uses high reaction temperatures, making it unsuitable for nanofiber production. The co-precipitation method also fails to produce a uniform precursor, making it difficult to produce nanofibers. Therefore, there is an urgent need to develop a method for uniformly preparing high-entropy zirconate fiber membranes. Summary of the Invention

[0005] In response to the deficiencies in the prior art, the first object of the present invention is to provide a nanoscale dual-phase high-entropy zirconate fiber membrane. Through the high-entropy structural design of the present invention, the fiber membrane has a dual-phase structure of pyrochlore and defective fluorite and a smaller grain size, so that the fiber membrane material has good sintering resistance, thermal insulation performance and high-temperature stability, while also having a certain degree of flexibility.

[0006] The second object of the present invention is to provide a method for preparing a nanoscale dual-phase high-entropy zirconate fiber membrane. The method determines a rare earth (RE)-zirconium (Zr) precursor suitable for preparing the fiber membrane, and explores the electrospinning conditions and heat treatment process. It can synthesize nanoscale high-entropy zirconate fiber membrane materials with uniform composition, good continuity, high oxide content at low temperature.

[0007] In order to achieve the above technical objectives, the present invention provides a nanoscale dual-phase high entropy zirconate fiber membrane, which is composed of continuous high entropy zirconate fibers; the chemical structure of the high entropy zirconate fibers is (La 0.2 Sm 0.2 Gd 0.2 Dy 0.2 Yb 0.2 )2Zr2O7, and it contains a dual-phase structure of pyrochlore and defective fluorite.

[0008] The key to the technical solution of the present invention lies in the use of specific alloying elements. The rare earth elements selected in the present invention simultaneously include light rare earths (La, Sm, and Gd) and heavy rare earths (Dy and Yb), with a high degree of dimensional disorder of up to 8.911, which is prone to form a pyrochlore and defective fluorite dual-phase structure. Through the high-entropy modification design of zirconate, the dual-phase high-entropy zirconate material prepared in the present invention has both high-entropy effect, lattice distortion effect, sluggish diffusion effect, and "cocktail" effect. Among them, the presence of a large number of grain boundaries and hetero-interfaces has achieved a substantial improvement in the anti-sintering performance and high-temperature stability of the zirconate material. And the present invention uses the electrospinning method to prepare the high-entropy zirconate material into a fibrous membrane form, which further improves the heat insulation performance of the material and reduces its density. In the dual-phase high-entropy zirconate fibrous membrane, the growth of zirconate particles is slow, and the smaller grain size is beneficial to improving the strength of the fiber. At the same time, the synchronous introduction of light rare earths and heavy rare earths makes the high-entropy zirconate fibrous membrane have two-phase structures, and the rich hetero-grain boundaries inside ensure that the fibrous membrane has good flexibility.

[0009] As a preferred solution, the grain size of the high-entropy zirconate fiber is 5-20 nm. The fine nanocrystals of the present invention have a higher specific surface area, and the high-density grain boundaries can effectively improve the strength and toughness of the material.

[0010] As a preferred solution, the thermal conductivity of the nano-scale dual-phase high-entropy zirconate fibrous membrane at room temperature is less than 0.035 W / m / K. The fibrous membrane material of the present invention has excellent heat insulation performance.

[0011] The second object of the present invention is to provide a method for preparing a nano-scale dual-phase high-entropy zirconate fibrous membrane, which method comprises the following steps:

[0012] (1) Weigh five rare earth metal salts of La, Sm, Gd, Dy, and Yb respectively, mix them with Zr salt, dissolve them with an organic solvent, and then add a spinning aid to obtain a RE-Zr precursor spinning solution;

[0013] (2) Electrospin the RE-Zr precursor spinning solution to obtain continuous high-entropy zirconate fibers, and receive the precursor fibrous membrane through a receiver;

[0014] (3) Heat-treat the precursor fibrous membrane in an oxygen-containing atmosphere to obtain the product.

[0015] Another key factor of the technical solution of the present invention lies in the adoption of the electrospinning-calcination method. By preparing a spinnable RE-Zr precursor spinning solution, the atomic and molecular-level mixing of alloying elements is achieved during the preparation of the precursor, and the obtained high-entropy zirconate material has a more uniform composition. The high-entropy zirconate fiber membrane precursor is obtained by electrospinning, and the rapid growth of grains is avoided during the subsequent calcination process, thereby damaging its anti-sintering performance and heat insulation performance.

[0016] As a preferred solution, the organic solvent is at least one of anhydrous methanol, anhydrous ethanol, acetone, and N,N-dimethylformamide; the spinning aid is polyethylene oxide and / or polyvinylpyrrolidone. Further preferably polyvinylpyrrolidone. Compared with polyvinylpyrrolidone, polyethylene oxide has a higher viscosity, which easily causes nozzle blockage and is not conducive to spinning. Moreover, polyvinylpyrrolidone is easily soluble in various solvents, and the solution preparation is more flexible.

[0017] As a preferred solution, the molar ratio of La, Sm, Gd, Dy, Yb, and Zr in the RE-Zr precursor spinning solution is 1:1:1:1:1:5.

[0018] As a preferred solution, the Zr salt is ZrOCl2 and its hydrates. The zirconium salt raw material used in the present invention is easily available and can be uniformly mixed with five rare earth metal salts in an organic solvent, greatly simplifying the process steps.

[0019] As a preferred solution, the mass ratio of the total mass of the five rare earth metal salts and the Zr salt to the mass of the organic solvent is 1:(1.6 - 3.3); the dosage of the spinning aid is 5 - 10 wt% of the mass of the RE-Zr precursor spinning solution. When the dosage of the organic solvent in the present invention is relatively high, the oxide content in the obtained high-entropy zirconate fibers is relatively low, the fiber diameters are uneven, and most of the fibers are short fibers, making it difficult to form a dense fiber. There are also problems of uneven fiber diameters and easy fracture in the fiber membrane after heat treatment. When the content of the organic solvent is relatively low, the spinning requirements cannot be met.

[0020] As a preferred solution, the electrospinning conditions are: relative humidity of 30-60%, temperature of 20-40°C, spinning voltage of 15-20KV, receiving distance of 10-20cm, propulsion speed of 0.3-0.7ml / h; the receiving device is a metal roller with a rotation speed of 100-300r / min. In the high-entropy zirconate fiber membrane system of the present invention, a slower propulsion speed and a slower rotation speed are required during the electrospinning process. When the propulsion speed is too fast, a bead-shaped precursor fiber membrane is easily formed, and the fiber diameter and composition are uneven. When the rotation speed is too fast, the diameter of the prepared precursor fiber membrane is small, the fiber diameter is uneven, and a large number of fibers are broken. In addition, the high spinning drum rotation speed causes the fibers to be overstretched, the fibers are shorter, and the flexibility of the fiber membrane is poor.

[0021] As a preferred embodiment, the heat treatment temperature ramp is as follows: from room temperature to 1100-1200°C at a rate of 1-5°C / min, held for 120-300 minutes, then reduced to 400-500°C at a rate of 2-3°C / min, followed by furnace cooling. The linear temperature ramp employed in the present invention facilitates the formation of uniform fiber morphology and helps control the slow growth of grains.

[0022] As a preferred solution, in step (1), after adding the spinning aid, stirring and aging for 12 to 72 hours are required. The stirring process can ensure that the rare earth salt and the zirconium salt are fully mixed, the spinning aid is fully dissolved, and the generation of slag balls during the spinning process is avoided.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The present invention provides a preparation scheme for high-entropy zirconate fiber membrane for the first time. The diameter of the prepared high-entropy zirconate fiber is controllable, the fiber continuity is good, it has certain flexibility, and it can be bent and folded.

[0025] (2) The process for preparing the spinnable rare earth-zirconium precursor spinning solution of the present invention is simple, the precursor has stable properties and can be stored for a long time.

[0026] (3) The rare earth elements selected by the present invention include both light rare earths (La, Sm, and Gd) and heavy rare earths (Dy and Yb), and their size disorder is as high as 8.911, which easily forms a dual-phase structure of pyrochlore and defective fluorite. As a result, the dual-phase high-entropy zirconate fiber prepared by the present invention contains a large number of grain boundaries and heterogeneous interfaces, thereby improving the material's sintering resistance and high-temperature stability. The high-entropy zirconate fiber membrane prepared by the alloying elements and preparation method of the present invention has uniform composition, extremely high purity, uniform diameter, and dense structure. Its grain size is within 20nm at high temperature, and it has good sintering resistance, thermal insulation performance, and high-temperature stability. Its thermal conductivity at room temperature is as low as 0.0332W / m / K.

[0027] (4) The present invention does not require complex heat treatment processes or atmosphere protection, and has a simple preparation process, which is easy for batch production. Description of the Drawings

[0028] Figure 1 It is a process flow chart for preparing a nanoscale dual-phase high-entropy zirconate fiber membrane according to the present invention.

[0029] Figure 2 XRD pattern of the nanoscale dual-phase (La 0.2 Sm 0.2 Gd 0.2 Dy 0.2 Yb 0.2 )2Zr2O7 fiber membrane prepared in Example 1.

[0030] Figure 3 Optical photograph of the nanoscale dual-phase (La 0.2 Sm 0.2 Gd 0.2 Dy 0.2 Yb 0.2 )2Zr2O7 fiber membrane prepared in Example 1.

[0031] Figure 4 SEM image of the nanoscale dual-phase (La 0.2 Sm 0.2 Gd 0.2 Dy 0.2 Yb 0.2 )2Zr2O7 fiber membrane prepared in Example 1.

[0032] Figure 5 TEM image and elemental distribution map of the nanoscale dual-phase (La 0.2 Sm 0.2 Gd 0.2 Dy 0.2 Yb 0.2 )2Zr2O7 fiber membrane prepared in Example 1.

[0033] Figure 6 Thermal insulation performance of the nanoscale dual-phase (La 0.2 Sm 0.2 Gd 0.2 Dy 0.2 Yb 0.2 )2Zr2O7 fiber membrane prepared in Example 1.

[0034] Figure 7 Thermal insulation performance of the nanoscale dual-phase (La 0.2 Sm 0.2 Gd 0.2 Dy 0.2 Yb 0.2)High-temperature stability of 2Zr2O7 fiber membrane. Detailed implementation mode

[0035] To further illustrate the present invention, the content of the present invention will be described in detail below in conjunction with embodiments. However, it should be understood that these embodiments are implemented on the premise of the technical solution of the present invention, and the detailed implementation methods and specific operation processes are given. It is only to further illustrate the features and advantages of the present invention, rather than a limitation on the claims of the present invention. The protection scope of the present invention is not limited to the following embodiments.

[0036] In the embodiments and comparative examples of the present invention, the receiving device for electrospinning all uses a metal roller.

[0037] Example 1

[0038] 1) Weigh equal molar amounts of 5 rare earth nitrate particles of La(NO3)3·6H2O, Sm(NO3)3·6H2O, Gd(NO3)3·6H2O, Dy(NO3)3·6H2O, and Yb(NO3)3·5H2O and mix them evenly, denoted as D RE ;

[0039] 2) Weigh the corresponding amount of ZrOCl2·8H2O according to the molar ratio of RE:Zr being 1:1, and mix it with D RE thoroughly, denoted as D RE-Zr .

[0040] 3) According to the mass ratio of the mixed salt D RE-Zr and the solvent being 1:2.7, weigh the corresponding amount of N,N-dimethylformamide, and dissolve the mixed salt D RE-Zr in DMF, stir for 5 h until D RE-Zr is fully dissolved, denoted as S RE-Zr .

[0041] 4) According to the content of the spinning aid being 7% of the mass of the S RE-Zr solution, weigh the corresponding amount of polyvinylpyrrolidone (PVP) and add it to the S RE-Zr solution and stir until fully dissolved. The stirring and aging time is 48 h to obtain a spinnable precursor spinning solution, denoted as A.

[0042] 5) Electrospin the precursor spinning solution A in step 4 under the spinning conditions of a temperature of 30 °C, a relative humidity of 40%, a rotation speed of the roller receiving device of 250 r / min, a spinning voltage of 15.5 KV, a receiving distance of 15 cm, and a feeding speed of 0.35 ml / h to obtain continuous high-entropy zirconate fibers. The precursor fiber membrane is obtained by receiving with a receiver. The prepared precursor fiber membrane has the characteristics of uniform fiber diameter and good fiber continuity.

[0043] 6) Heat-treat the precursor fiber membrane B spun in step 5 in an air atmosphere at 1100 °C for 2 h to obtain a nano-biphasic high-entropy zirconate fiber membrane. The fiber structure is dense, and the fiber diameter is small, ranging from 150 to 400 nm. The heat treatment procedure is as follows: heat from room temperature to 1100 °C at a heating rate of 5 °C / min, then hold for 2 h, then cool to 500 °C at a cooling rate of 2 °C / min, and then cool in the furnace to room temperature.

[0044] Test the thermal insulation performance of the (La 0.2 Sm 0.2 Gd 0.2 Dy 0.2 Yb 0.2 )2Zr2O7 fiber membrane with a thickness of 8 mm using a butane flame (1380 °C). After 300 s of heat treatment, its back temperature is only 259 °C. Its thermal conductivity at room temperature is only 0.332 W / m / K. It has good thermal insulation performance. The grain size in the high-entropy zirconate fiber is 5 - 20 nm. After heat treatment at 1100 °C for 10 h, the grain size slightly increases to 50 - 80 nm, indicating that the prepared fiber membrane has good anti-sintering performance. In addition, the fiber membrane also has good high-temperature phase stability and still maintains the fluorite and pyrochlore biphasic structure after heat treatment at 1200 °C for 10 h. At the same time, it Figure 3 can be confirmed that the fiber membrane material has a certain flexibility.

[0045] Example 2

[0046] 1) Weigh equal molar amounts of 5 rare earth nitrate particles of La(NO3)3·6H2O, Sm(NO3)3·6H2O, Gd(NO3)3·6H2O, Dy(NO3)3·6H2O, and Yb(NO3)3·5H2O and mix them evenly, denoted as D RE ;

[0047] 2) Weigh the corresponding amount of ZrOCl2·8H2O according to the molar ratio of RE:Zr being 1:1, and mix it fully with D RE and denote it as D RE-Zr .

[0048] 3) According to the mass ratio of the mixed salt D RE-Zr and the solvent being 1:2, weigh the corresponding amount of N,N-dimethylformamide, dissolve the mixed salt D RE-Zr in DMF, and stir for 5 h until D RE-Zr is fully dissolved, denoted as S RE-Zr .

[0049] 4) According to the content of the spinning aid being 5% of the mass of the S RE-Zr solution, weigh the corresponding amount of polyvinylpyrrolidone (PVP) and add it to S RE-ZrStir in the solution until it is fully dissolved. The stirring aging time is 48 h to obtain a spinnable precursor spinning solution, denoted as A.

[0050] 5) Electrospin the precursor spinning solution A in step 4 under the spinning conditions of a temperature of 30 °C, a relative humidity of 40%, a rotational speed of the drum receiving device of 250 r / min, a spinning voltage of 15.5 kV, a receiving distance of 15 cm, and a feeding speed of 0.35 ml / h to obtain continuous high-entropy zirconate fibers, which are received by the receiver to obtain a precursor fiber membrane B.

[0051] 6) Sinter the precursor fiber membrane B spun in step 5 in an air atmosphere. The heat treatment procedure is as follows: heat from room temperature to 1000 °C at a heating rate of 5 °C / min, then hold for 2 h, then cool to 500 °C at a cooling rate of 2 °C / min, and then cool to room temperature in the furnace to obtain a nano high-entropy zirconate fiber membrane.

[0052] Test the heat insulation performance of the (La 0.2 Sm 0.2 Gd 0.2 Dy 0.2 Yb 0.2 )2Zr2O7 fiber membrane with a thickness of 8 mm using a butane flame (1380 °C). After heat treatment for 300 s, its back temperature is only 262 °C. Its thermal conductivity at room temperature is only 0.0340 W / m / K. It has good heat insulation performance. The grain size of the high-entropy zirconate fiber is 5 - 20 nm. After heat treatment at 1100 °C for 10 h, the grain size slightly increases to 50 - 90 nm, indicating that the prepared fiber membrane has good anti-sintering performance. In addition, the fiber membrane also has good high-temperature phase stability and still maintains the fluorite and pyrochlore double-phase structure after heat treatment at 1200 °C for 10 h.

[0053] Example 3

[0054] 1) Weigh 5 kinds of rare earth nitrate particles of equimolar amounts of La(NO3)3·6H2O, Sm(NO3)3·6H2O, Gd(NO3)3·6H2O, Dy(NO3)3·6H2O, and Yb(NO3)3·5H2O and mix them evenly, denoted as D RE ;

[0055] 2) Weigh the corresponding amount of ZrOCl2·8H2O according to the molar ratio of RE:Zr of 1:1, and mix it fully with D RE to obtain D RE-Zr .

[0056] 3) According to the mass ratio of the mixed salt D RE-Zr and the solvent of 1:2.7, weigh the corresponding amount of N,N-dimethylformamide, and mix the mixed salt D RE-ZrDissolve it in DMF and stir for 5 h until D RE-Zr is fully dissolved and denoted as S RE-Zr .

[0057] 4) According to the content of the spinning aid being S RE-Zr which is 7% of the solution mass, weigh out the corresponding amount of polyvinylpyrrolidone (PVP) and add it to S RE-Zr solution and stir until fully dissolved. The stirring and aging time is 48 h to obtain a spinnable precursor spinning solution, denoted as A.

[0058] 5) Electrospin the precursor spinning solution A in step 4 under the spinning conditions of a temperature of 40 °C, a relative humidity of 40%, a rotational speed of the drum receiving device of 300 r / min, a spinning voltage of 16 kV, a receiving distance of 12 cm, and a feeding speed of 0.5 ml / h to obtain continuous high-entropy zirconate fibers, which are received by the receiver to obtain a precursor fiber membrane B.

[0059] 6) Heat-treat the precursor fiber membrane B spun in step 5 in an air atmosphere. The heat-treatment procedure is as follows: heat from room temperature to 1100 °C at a heating rate of 5 °C / min, then hold for 2 h, then cool at a cooling rate of 2 °C / min to 500 °C, and then cool to room temperature with the furnace to obtain a nano-high-entropy zirconate fiber membrane.

[0060] Test the heat insulation performance of the (La 0.2 Sm 0.2 Gd 0.2 Dy 0.2 Yb 0.2 )2Zr2O7 fiber membrane with a thickness of 8 mm using a butane flame (1380 °C). After heat treatment for 300 s, its back temperature is only 260 °C. Its thermal conductivity at room temperature is only 0.0335 W / m / K. It has good heat insulation performance. The grain size in the high-entropy zirconate fiber is 5 - 20 nm. After heat treatment at 1100 °C for 10 h, the grain size slightly increases to 50 - 80 nm, indicating that the prepared fiber membrane has good anti-sintering performance. In addition, the fiber membrane also has good high-temperature phase stability and still maintains the fluorite and pyrochlore double-phase structure after heat treatment at 1200 °C for 10 h.

[0061] Example 4

[0062] 1) Weigh out equimolar amounts of 5 rare earth nitrate particles of La(NO3)3·6H2O, Sm(NO3)3·6H2O, Gd(NO3)3·6H2O, Dy(NO3)3·6H2O, and Yb(NO3)3·5H2O and mix them evenly, denoted as D RE

[0063] 2) Weigh the corresponding amount of ZrOCl2·8H2O according to the molar ratio of RE:Zr being 1:1, and mix it fully with D RE and label it as D RE-Zr .

[0064] 3) According to the mass ratio of the mixed salt D RE-Zr to the solvent being 1:2.7, weigh the corresponding amount of N,N-dimethylformamide, dissolve the mixed salt D RE-Zr in DMF, and stir for 5 h until D RE-Zr is fully dissolved, and label it as S RE-Zr .

[0065] 4) According to the content of the spinning aid being 7% of the mass of the S RE-Zr solution, weigh the corresponding amount of polyvinylpyrrolidone (PVP), add it to the S RE-Zr solution and stir until it is fully dissolved. The stirring and aging time is 48 h to obtain a spinnable precursor spinning solution, which is labeled as A.

[0066] 5) Electrospinning is carried out on the precursor spinning solution A in step 4 under the spinning conditions of a temperature of 30 °C, a relative humidity of 30%, a rotation speed of the roller receiving device of 250 r / min, a spinning voltage of 15.5 KV, a receiving distance of 15 cm, and a feeding speed of 0.35 ml / h to obtain continuous high-entropy zirconate fibers, and the precursor fiber membrane B is obtained through receiving by the receiver.

[0067] 6) The precursor fiber membrane B spun in step 5 is heat-treated in an air atmosphere. The heat treatment procedure is as follows: heat from room temperature to 1200 °C at a heating rate of 5 °C / min, then hold for 2 h, then cool down to 500 °C at a cooling rate of 2 °C / min, and then cool to room temperature in the furnace to obtain a nano-high-entropy zirconate fiber membrane.

[0068] Test the heat insulation performance of the (La 0.2 Sm 0.2 Gd 0.2 Dy 0.2 Yb 0.2 )2Zr2O7 fiber membrane with a thickness of 8 mm using a butane flame (1380 °C). After heat treatment for 300 s, its back temperature is only 264 °C. Its thermal conductivity at room temperature is only 0.0341 W / m / K, showing good heat insulation performance. After heat treatment at 1100 °C for 10 h, the grain size slightly increases to 50 - 100 nm, indicating that the prepared fiber membrane has good anti-sintering performance. In addition, the fiber membrane also has good high-temperature phase stability and still maintains the fluorite and pyrochlore double-phase structure after heat treatment at 1200 °C for 10 h.

[0069] Comparative Example 1

[0070] 1) According to the molar ratio of Yb:Zr being 1:1, weigh the corresponding amount of Yb(NO3)3·5H2O and ZrOCl2·8H2O raw materials and mix them thoroughly, which is recorded as D Yb-Zr .

[0071] 2) According to the mixed salt D Yb-Zr The mass ratio of the solvent is 1:2.7, and the corresponding amount of N,N-dimethylformamide is weighed and the mixed salt D Yb-Zr Dissolve in DMF and stir for 5 h until D Yb-Zr Fully dissolved, recorded as S Yb-Zr .

[0072] 3) According to the content of spinning aid S Yb-Zr 7% of the solution mass, weigh the corresponding amount of polyvinyl pyrrolidone (PVP) and add S RE-Zr The solution was stirred until fully dissolved, and the stirring aging time was 48 h to obtain a spinnable precursor spinning solution, which was recorded as A.

[0073] 4) The precursor spinning solution A of step 3 is electrospun under the spinning conditions of temperature 30°C, relative humidity 40%, drum receiving device speed 250r / min, spinning voltage 15.5KV, receiving distance 15cm, and propulsion speed 0.35ml / h to obtain continuous fibers, which are received by the receiver to obtain precursor fiber membrane B.

[0074] 5) The precursor fiber membrane B spun in step 4 was heat-treated at 1100°C for 2 h in an air atmosphere to obtain an ytterbium zirconate fiber membrane. The heat treatment procedure was as follows: heating from room temperature to 1100°C at a rate of 5°C / min, then keeping the temperature for 2 h, then cooling to 500°C at a rate of 2°C / min, and then cooling to room temperature in the furnace.

[0075] Compared with Example 1, the structure of the ytterbium zirconate fiber membrane is denser, but the fiber diameter is about 500 nm, which is larger, the particle size is larger, and the sintering resistance is poor.

[0076] Comparative Example 2

[0077] Steps 1 to 4 and step 6 of this comparative example are the same as those of Example 1, except that:

[0078] 5) The precursor spinning solution A of step 4 is electrospun under the spinning conditions of 30°C, 40% relative humidity, 250r / min rotation speed of the drum receiving device, 12kV spinning voltage, 15cm receiving distance, and 0.35ml / h propulsion speed to obtain a precursor fiber membrane B.

[0079] Compared with Example 1, there are a large number of fiber fusions in the obtained high-entropy zirconate precursor fiber membrane, the fiber diameters are uneven, and there are slag balls. After heat treatment, the fiber membrane also has uneven fiber diameters and is prone to breakage.

[0080] Comparative Example 3

[0081] Steps 1-2 and steps 4-6 of this comparative example are the same as those in Example 1, and the difference lies only in the following steps:

[0082] 3) According to the mass ratio of mixed salt D RE-Zr to the solvent being 1:6, weigh the corresponding amount of N,N-dimethylformamide, and dissolve mixed salt D RE-Zr in DMF and stir for 5 h until D RE-Zr is fully dissolved, denoted as S RE-Zr .

[0083] Compared with Example 1, the obtained high-entropy zirconate fibers have a lower oxide content, uneven fiber diameters, and most of the fibers are short fibers, making it difficult to form a dense fiber. After heat treatment, the fiber membrane also has uneven diameters and is prone to breakage.

[0084] Comparative Example 4

[0085] Steps 1-4 and step 6 of this comparative example are the same as those in Example 1, and the difference lies only in the following steps:

[0086] 5) Electrospinning the precursor spinning solution A in step 4 under the spinning conditions of a temperature of 30 °C, a relative humidity of 40%, a drum receiving device rotation speed of 500 r / min, a spinning voltage of 15.5 KV, a receiving distance of 15 cm, and a feeding speed of 0.35 ml / h to obtain continuous high-entropy zirconate fibers, and obtaining a precursor fiber membrane B through receiver reception.

[0087] Compared with Example 1, the fibers in the prepared precursor fiber membrane have smaller diameters, uneven fiber diameters, and a large number of fiber breaks. The high rotating speed of the take-up bobbin causes excessive stretching of the fibers, the fibers are shorter and the flexibility of the fiber membrane is poor.

Claims

1. A nanoscale dual-phase high-entropy zirconate fiber membrane, characterized in that: Composed of continuous high-entropy zirconate fibers; the chemical structural formula of the high-entropy zirconate fibers is (La 0.2 Sm 0.2 Gd 0.2 Dy 0.2 Yb 0.2 )2Zr2O7, and it contains a pyrochlore and defective fluorite biphasic structure.

2. The nanoscale dual-phase high-entropy zirconate fiber membrane according to claim 1, wherein: The grain size of the high-entropy zirconate fiber is 5-20 nm.

3. The nanoscale dual-phase high-entropy zirconate fiber membrane according to claim 1 or 2, characterized in that: The thermal conductivity of the nanoscale dual-phase high-entropy zirconate fiber membrane at room temperature is less than 0.035 W / m / K.

4. The preparation method of a nanoscale dual-phase high-entropy zirconate fiber membrane according to any one of claims 1 to 3, characterized in that: It includes the following steps: (1) Weigh the five rare earth metal salts of La, Sm, Gd, Dy, and Yb respectively, mix them with the Zr salt, dissolve them with an organic solvent, and then add a spinning aid to obtain a RE-Zr precursor spinning solution. (2) Electrospun the RE-Zr precursor spinning solution to obtain continuous high-entropy zirconate fibers, and the precursor fiber membrane is obtained by receiving with a receiver. (3) Heat-treat the precursor fiber membrane in an oxygen-containing atmosphere to obtain the product.

5. The preparation method of a nanoscale dual-phase high-entropy zirconate fiber membrane according to claim 4, characterized in that: The organic solvent is at least one of anhydrous methanol, anhydrous ethanol, acetone, and N,N-dimethylformamide; the spinning aid is polyethylene oxide and / or polyvinylpyrrolidone.

6. The preparation method of a nanoscale dual-phase high-entropy zirconate fiber membrane according to claim 4, characterized in that: In the RE-Zr precursor spinning solution, the molar ratio of La, Sm, Gd, Dy, Yb, and Zr is 1:1:1:1:1:

5.

7. The preparation method of a nanoscale dual-phase high-entropy zirconate fiber membrane according to claim 5 or 6, characterized in that: The mass ratio of the total mass of the five rare earth metal salts and the Zr salt to the mass of the organic solvent is 1:(1.6-3.3); the dosage of the spinning aid is 5-10 wt% of the mass of the RE-Zr precursor spinning solution.

8. The preparation method of a nanoscale dual-phase high-entropy zirconate fiber membrane according to claim 7, characterized in that: The conditions of the electrospinning are: relative humidity is 30-60%, temperature is 20-40 °C, spinning voltage is 15-20 KV, receiving distance is 10-20 cm, and the propulsion speed is 0.3-0.7 ml / h; the receiving device is a metal drum with a rotation speed of 100-300 r / min.

9. The preparation method of a nanoscale dual-phase high-entropy zirconate fiber membrane according to claim 4, characterized in that: The heating program of the heat treatment is: heating from room temperature to 1100-1200 °C at a rate of 1-5 °C / min, holding for 120-300 min; then cooling to 400-500 °C at a rate of 2-3 °C / min, and then cooling with the furnace.

10. The preparation method of a nanoscale dual-phase high-entropy zirconate fiber membrane according to claim 7, characterized in that: In the step (1), after adding the spinning aid, it needs to be stirred and aged for 12-72 h.

Citation Information

Patent Citations

  • Method for preparing zirconate yttrium nanofiber from zirconium-yttrium polymer precursor

    CN109868526A

  • Low-thermal-conductivity CMAS-corrosion-resistant high-entropy zirconate ceramic material as well as preparation method and application thereof

    CN115925417A

  • Zirconic acid rare earth-based high-entropy ceramic nanofiber as well as preparation method and application thereof

    CN114751737A

  • Nanoscale double-phase high-entropy zirconate material and preparation method thereof

    CN118405921A

Cited By

  • Fluorite-pyrochlore double-phase high-entropy oxide ceramic powder and preparation method thereof

    CN119100790A

  • Fluorite-hooperite dual-phase high-entropy oxide ceramic powder and preparation method thereof

    CN119100790B